Assuring justice in Malaysia: ensuring restorative justice in the Syariah courts - Wan Muhammad, Ramizah; Hussin, Nasimah; Abas, Afridah (2018)
The imposition of punishment in Malaysian Syariah Court practice is limited to only 3 years imprisonment, a RM5000 fine and 6 strokes of whipping. In most cases, the offender is punished with imprisonment and fine, whilst rarely be imposed with reformative nature of punishment. This research looks for the loop hole that needs to be reformed in such practice since the punishment in Islam is not only aimed to deter the offender, but also to reform the offender in all life aspects and to create a balance between the rights of the victim and the rights of the offender. In this situation, the concept and principles of restorative justice plays important part as the essential concept of restorative justice is in fact parallels with Quran and Sunnah. Apart from an urgent need for the explicit provision in the statutes, this research also calls for the inculcation of awareness among the Syariah Court Judges, Syariah prosecutors as well as Syariah practitioners on the importance of restorative justice in creating a harmonious society.